2020
DOI: 10.32900/2312-8402-2020-123-21-30
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Antibacterial Efficacy of Ethanolic Extracts From Aglaonema Commutatum Schott Leaves and Its Cultivars Against Escherichia Coli Strain

Abstract: This study aimed to evaluate the antibacterial activity of ethanolic extracts obtained from the leaves of Aglaonema commutatum Schott and its cultivars («Malay Beauty», «Silver Queen», and «Silver King») against Escherichia coli (Migula) Castellani and Chalmers (ATCC® 25922™) strain. The leaves of Aglaonema commutatum plants and its cultivars, cultivated under glasshouse conditions, were sampled at M. M. Gryshko National Botanic Garden (NBG), National Academy of Science of Ukraine (Kyiv, Ukraine). The leaves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Only extract derived from leaves of F. elastica 'Variegata' (5 mg.mL -1 ) caused the decrease in TBARS level (by 29.2% p <0.05) compared to untreated controls. Among extracts studied (0.5 mg.mL -1 ), F. elastica 'Burgundy' exhibited the lowest TBARS level (decreased by 33.5%, p <0.05) while in dose 5 mg.mL -1 , F. elastica 'Variegata' decreased TBARS level by 29.2% (p <0.05) (Opryshko et al, 2020).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Only extract derived from leaves of F. elastica 'Variegata' (5 mg.mL -1 ) caused the decrease in TBARS level (by 29.2% p <0.05) compared to untreated controls. Among extracts studied (0.5 mg.mL -1 ), F. elastica 'Burgundy' exhibited the lowest TBARS level (decreased by 33.5%, p <0.05) while in dose 5 mg.mL -1 , F. elastica 'Variegata' decreased TBARS level by 29.2% (p <0.05) (Opryshko et al, 2020).…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, in our previous study (Opryshko et al, 2020), we evaluated the in vitro possible antioxidant effects of extracts derived from leaves of F. elastica and its cultivars (Rubra, Robusta, Burgundy, Variegata) using oxidative stress biomarker [2-thiobarbituric acid reactive substances (TBARS) as a biomarker of lipid peroxidation] using of human erythrocytes as a cell model after incubation with plant extracts in two doses (5.0 and 0.5 mg.mL -1 ). Our results revealed that treatment of human erythrocytes by extracts derived from leaves of F. elastica and its cultivars 'Rubra' and 'Burgundy' in the dose of 0.5 mg.mL -1 caused a statistically significant decrease of TBARS level by 27.3% (p <0.05), 32.4% (p <0.05), and 33.5% (p <0.05), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we also investigated the antibacterial properties of ethanolic extracts derived from Aglaonema commutatum and its cultivars against various strains (Opryshko et al, 2019(Opryshko et al, , 2020a. In the current study, we used two Enterococcus faecalis strains, i.e.…”
Section: Introductionmentioning
confidence: 99%